The changing of the guards: Can physicians contain social insurance costs? - Simen Markussen; Knut Røed; Ole J. Røgeberg (Institute for the Study of Labor (IZA), 2013)
Based on administrative data from Norway, we examine the extent to which family doctors influence their clients' propensity to claim sick pay and disability benefits. The analysis is based on exogenous shifts of family doctors occurring when physicians quit, retire, or for other reasons sell their patient lists to other doctors. Our key finding is that family doctors have significant influence on their clients' benefit claims. We conclude that it is possible for family doctors to contain social insurance costs to some extent, and that there is a significant variation across doctors in the way they do so.
Keywords: H55; I13; 330; sick pay; disability insurance; absence certification; gatekeepers; Ärzte; Familie; Lohnfortzahlung; Erwerbsunfähigkeitsrente; Kontrolle; Norwegen